Bioactive porous ceramic material and production method thereof
By using bioactive porous ceramic materials composed of aluminate cement cementitious materials, low-temperature sintering and combining multiple premix and ramming forming processes, the problems of high sintering temperature and long cycle of existing filter materials for aquatics have been solved. It realizes high-strength and low-cost filter material production, suitable for fresh aquarium environment.
Patent Information
- Application Number
- CN202411602490.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-07
AI Technical Summary
The existing aquarium filter materials have high firing temperature, long firing cycle and high production costs, which restrict the development of the industry.
Bioactive porous ceramic materials composed of aluminate cement cementitious materials, bamboo fibers, aluminum dihydrogen phosphate, glue powder, starch ether, pearl sand, zeolite, expanded perlite powder, etc., are sintered by low temperature (550℃~580℃ ℃) production, combined with multiple premix and ramming forming processes, improve the porosity and strength of the material.
It achieves a low firing temperature, short cycle, stable product size and high strength, and the pore size and pure water flux meet filtration needs. It is suitable for fresh aquarium environment and improves biological activity and oxidative decomposition efficiency.
Smart Images

Figure CN119263759A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water ecological filtering materials, and in particular relates to a biologically active porous ceramic material and a production method thereof. Background Art
[0002] In recent years, the scale of fresh food and aquaculture has continued to grow. Whether it is aquaculture, tourism, or home water tanks and fish tank landscapes, they are all activities that bring nature to humans. They all need to be thoughtful and create a comfortable and suitable living environment for them. The ecological cycle environment of a fish tank, water tank, fish pond, and fish pond requires an internal circulation ecological environment of organisms, animals, microorganisms, water, oxygen, and sunlight. The filter material can filter the suspended matter of animal and plant life residues in the water, absorb heavy metals in the water, and provide a habitat for parasitic microorganisms (nitrifying bacteria house), degrade COD animal and plant life residues under the action of oxygen (oxygenation) and negative ion polarization, and convert toxic substances such as ammonia nitrogen into harmless substances such as non-toxic nano-titanium oxide.
[0003] Patent application CN201210567201.0 discloses a filter material for aquarium with high porosity and a preparation method thereof. The raw materials are prepared by mixing the ingredients, extruding, and drying, and then obtaining the finished product through a certain firing curve. The firing system includes: (1) uniformly heating from room temperature to 1080°C for 10 hours; (2) keeping the temperature at 1080°C for 1 hour; (3) uniformly cooling to 1050°C for 2 hours; (4) uniformly heating from 1050°C to 1080°C for 1 hour; (5) keeping the temperature at 1080°C for 2 hours; (6) uniformly cooling to room temperature for 8 hours to obtain the finished product.
[0004] Patent application CN202210038305.6 discloses a filter material for aquarium and a preparation method thereof. The filter material for aquarium includes the following components: 50-70 parts of perlite, 3-8 parts of feldspar, 6-10 parts of pearls, 3-7 parts of double fly powder, 1-3 parts of dolomite, 0.5-1 part of polyvinyl alcohol, and 3-8 parts of clay. The preparation method includes the following steps: mixing perlite, feldspar, pearl, double fly powder, dolomite, polyvinyl alcohol and clay uniformly and stirring to obtain a mixed ingredient; granulating the mixed ingredient, pressing and forming, and drying; uniformly heating from room temperature to 1280°C, with a uniform heating rate of 128°C per hour; keeping warm at 1280°C; cooling from 1280°C to 1150°C, and then uniformly cooling from 1150°C to room temperature to obtain a filter material for aquarium.
[0005] The above-mentioned aquarium filter materials have problems such as high firing temperature, long firing cycle, and high production cost, which restrict the development of the industry. Summary of the invention
[0006] The technical problem to be solved by the present invention is: to provide a bioactive porous ceramic material and a production method thereof in view of the deficiencies in the prior art.
[0007] In order to solve the above technical problems, the technical solution of the present invention is:
[0008] A bioactive porous ceramic material comprises the following components, measured in parts by weight: 8-20 parts of aluminate cement gelling material, 1.0-2.0 parts of bamboo fiber, 1-7 parts of aluminum dihydrogen phosphate, 1-2 parts of rubber powder, 0.1-0.5 parts of starch ether, 0.1-0.5 parts of nano titanium oxide, 60-80 parts of pearl sand, 5-10 parts of zeolite powder, 7-20 parts of expanded pearlite powder and 18-22 parts of water.
[0009] As a preferred embodiment of the above technical solution, the aluminate cement has an alumina content of CA50 and a strength grade of CA50-II. The model is CA50, the alumina content is greater than or equal to 50%, and the strength grade is CA50-II (implementing GB / T 201-2015), and the aluminate cement can also be directly changed to the model of CA50-II.
[0010] As a preferred embodiment of the above technical solution, the pearl sand particle size is 70 mesh to 140 mesh, and the bulk density is 1567 kg / m 3 .
[0011] The admixture in the above technical solution includes zeolite, expanded perlite powder, etc., which are used as pore formers and lightweight aggregates.
[0012] As a preferred embodiment of the above scheme, the zeolite powder is clinoptilolite produced in Shangtianti, Xinyang, and the fineness (residue on a 100-mesh square sieve) should be less than 10%.
[0013] As a preferred embodiment of the above scheme, the bulk density of the expanded perlite powder should be less than 130 kg / m 3 The fineness (residue on 100 mesh square hole sieve) should be less than 10%.
[0014] As a preferred embodiment of the above technical solution, the bamboo fiber has a fiber length of 5 to 10 mm and a diameter of 20 to 30 μm. The bamboo fiber plays a role in resisting cracking and increasing the open porosity.
[0015] As a preferred embodiment of the above technical solution, the aluminum dihydrogen phosphate is a white powder with a relative density of 2.19 g / cm 3 .
[0016] The starch ether in the above technical solution includes but is not limited to hydroxyalkyl starch ether, carboxymethyl starch ether and cationic starch ether. As a preferred embodiment of the above technical solution, the hydroxyalkyl starch ether has a viscosity of 100000 mPa·s and a fineness of 80-100 meshes.
[0017] As a preferred embodiment of the above technical solution, the nano titanium is a white loose powder, the crystal form is anatase, the particle size is 10 nanometers, the purity is greater than 99.9%, and the specific surface area is 70 to 90 m 2 / g.
[0018] The rubber powder is a dispersible rubber powder. As a preferred embodiment of the above technical solution, the redispersible latex powder is produced by Wacker Chemical (Nanjing) Co., Ltd. 4018N type redispersible latex powder, usage amount not less than 1.0%.
[0019] A bioactive porous ceramic material, the production method of which comprises the following steps:
[0020] Step 1: Prepare the masterbatch. Accurately measure the aluminate cement cementitious material, bamboo fiber, aluminum dihydrogen phosphate, rubber powder, starch ether, and nano-titanium oxide, stir and mix them evenly in a mixer, accurately measure, and package them for storage.
[0021] Step 2: Prepare the batch material. Accurately measure the masterbatch, pearl sand, zeolite, and expanded perlite powder, stir and mix them evenly in a mixer, accurately measure, and package them for storage.
[0022] Step 3: Molding. Assemble the mold, calculate the amount of ingredients, add the ingredients and water into the mortar mixer, stir for 3 minutes, let stand for 10 minutes, continue stirring for 2 minutes, add to the mold, and tamp with a micro vibrator. After 7 days, remove the mold to obtain the blank.
[0023] Step 4: Drying and firing. After the blank is cured for 7 days, it is dried and dehydrated in a dryer at 100℃~110℃ for 8 hours. The dried and dehydrated blank enters the roller kiln for low-temperature firing. During firing, the blank is stacked in a refractory sagger. The firing cycle is 0.5~1 hour, and the maximum temperature is 550℃~580℃. The following reactions will occur during firing:
[0024] Reaction 1: Physical water removal from cement stone, aluminum dihydrogen phosphate, zeolite, bamboo fiber, and expanded perlite powder at 100℃ to 300℃, and the porosity of the dehydrated blank increases;
[0025] Reaction 2: 300-580℃ hydrated calcium hydroxide in cement stone dehydrates and forms active calcium phosphate with aluminum polyphosphate after dehydration of aluminum dihydrogen phosphate, increasing the porosity and strength of the blank; bound water in pearl sand is released;
[0026] Reaction 3: Keep warm at 580℃, dehydrate pearl sand, carbonize bamboo fiber, and sinter in the presence of a small amount of glass liquid phase and aluminum polyphosphate to ensure sintered size, strength, activity and porosity.
[0027] Step 5: Testing. Test the size, pore size of the filter material, bulk density, bending strength, water absorption, pure water permeability, pH value of the 24-hour immersion water solution, and dissolved oxygen concentration.
[0028] The beneficial effects of the present invention are:
[0029] The present invention provides a kind of bioactive porous ceramic material, including aluminate cement, pearl sand, zeolite, alumina powder, expanded perlite powder, bamboo fiber, aluminum dihydrogen phosphate, rubber powder, starch ether, nano titanium oxide and other components, wherein the gelling material includes aluminate cement, zeolite, aluminum phosphate, rubber powder, starch ether, the aggregate is pearl sand, zeolite, alumina powder, expanded perlite powder are mineral admixtures, and nano titanium is a negative ion photocatalyst, which can decompose oxygen in water and air into oxygen anions under the action of sunlight or ultraviolet rays, increase the oxygen concentration of water and accelerate the oxidation and decomposition of organic matter. The gelling and plastic components in the material components are combined in an organic and inorganic, mineral and compound manner, which ensures the strength and molding performance of the blank during production. During production, the masterbatch is first prepared, and then the batch is prepared. The batch is premixed multiple times to ensure the uniformity and stability of the batch. The molding is formed by ramming and pouring, and then it is cured and shaped, dried and fired to dehydrate, produce liquid phase and in-situ new crystal phase, improve the mechanical strength of the filter material, and ensure the size and filtration aperture.
[0030] The production of the present invention has low firing temperature and short cycle, and the product has stable size and high strength. The pore size and pure water flux meet the filtering requirements. The pH value of the immersion liquid is weakly alkaline and the dissolved oxygen concentration of the water is increased. It is suitable for the survival of fresh food and aquatic nitrifying bacteria and improves biological activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a process flow chart for the production of bioactive porous ceramic materials for fresh food and aquarium filtration. DETAILED DESCRIPTION
[0032] In order to explain the technical content, structural features, achieved objectives and effects of the technical solution in detail, the following is a detailed description in conjunction with specific embodiments and accompanying drawings.
[0033] Example 1
[0034] A bioactive porous ceramic material comprises the following components, measured by weight: 10 parts of aluminate cement gelling material, 2.0 parts of bamboo fiber, 4 parts of aluminum dihydrogen phosphate, 1.5 parts of rubber powder, 0.5 parts of starch ether, 0.1 parts of nano titanium oxide, 60 parts of pearl sand, 10 parts of zeolite, 20 parts of expanded pearlite powder and 20 parts of water.
[0035] Aluminate cement, alumina content is CA50, strength grade is CA50-II. Model is CA50, alumina content is greater than or equal to 50%, strength grade is CA50-II (implement GB / T 201-2015), and can also be directly changed to the aluminate cement model CA50-II.
[0036] The particle size of pearl sand is 70 mesh to 140 mesh, and the bulk density is 1567 kg / m 3 Admixtures, including zeolite, expanded perlite powder, etc., are used as pore formers and lightweight aggregates. Among them, the zeolite powder is clinoptilolite produced in Shangtianti, Xinyang, and the fineness (100 mesh square hole sieve residue) should be less than 10%. The bulk density of expanded perlite powder should be less than 130 kg / m 3 The fineness (residue on 100 mesh square hole sieve) should be less than 10%.
[0037] Bamboo fiber, fiber length 5 ~ 10mm, diameter 20 ~ 30μm. Bamboo fiber plays a role in crack resistance and increasing the open porosity. Aluminum dihydrogen phosphate is a white powder with a relative density of 2.19g / cm 3 The starch ethers include but are not limited to hydroxyalkyl starch ethers, carboxymethyl starch ethers and cationic starch ethers. As a preferred embodiment of the above technical solution, the hydroxyalkyl starch ether has a viscosity of 100000 mPa·s and a fineness of 80 to 100 meshes.
[0038] Nano titanium is a white loose powder with anatase crystal form, a particle size of 10 nanometers, a purity greater than 99.9%, and a specific surface area of 70 to 90 m 2 / g. The rubber powder is dispersible rubber powder, and the redispersible latex powder is produced by Wacker Chemical (Nanjing) Co., Ltd. 4018N type redispersible latex powder, usage amount not less than 1.0%.
[0039] A bioactive porous ceramic material, the production method of which comprises the following steps:
[0040] Step 1: Prepare the masterbatch. Accurately measure the aluminate cement cementitious material, bamboo fiber, aluminum dihydrogen phosphate, rubber powder, starch ether, and nano-titanium oxide, stir and mix them evenly in a mixer, accurately measure, and package them for storage.
[0041] Step 2: Prepare the batch material. Accurately measure the masterbatch, pearl sand, zeolite, and expanded perlite powder, stir and mix them evenly in a mixer, accurately measure, and package them for storage.
[0042] Step 3: Molding. Assemble the mold, calculate the amount of ingredients, add the ingredients and water into the mortar mixer, stir for 3 minutes, let stand for 10 minutes, continue stirring for 2 minutes, add to the mold, and tamp with a micro vibrator. After 7 days, remove the mold to obtain the blank.
[0043] Step 4: Drying and firing. After the blank is cured for 7 days, it is dried and dehydrated in a dryer at 100℃~110℃ for 8 hours. The dried and dehydrated blank enters the roller kiln for low-temperature firing. During firing, the blank is stacked in a refractory sagger. The firing cycle is 0.5~1 hour, and the maximum temperature is 550℃~580℃. The following reactions will occur during firing:
[0044] Reaction 1: Physical water removal from cement stone, aluminum dihydrogen phosphate, zeolite, bamboo fiber, and expanded perlite powder at 100℃ to 300℃, and the porosity of the dehydrated blank increases;
[0045] Reaction 2: 300-580℃ hydrated calcium hydroxide in cement stone dehydrates and forms active calcium phosphate with aluminum polyphosphate after dehydration of aluminum dihydrogen phosphate, increasing the porosity and strength of the blank; bound water in pearl sand is released;
[0046] Reaction 3: Keep warm at 580℃, dehydrate pearl sand, carbonize bamboo fiber, and sinter in the presence of a small amount of glass liquid phase and aluminum polyphosphate to ensure sintered size, strength, activity and porosity.
[0047] Step 5: Testing. Test the size, pore size of the filter material, bulk density, bending strength, water absorption, pure water permeability, pH value of the 24-hour immersion water solution, and dissolved oxygen concentration.
[0048] Example 2
[0049] A bioactive porous ceramic material comprises the following components by weight: 8 parts of aluminate cement gelling material, 2.0 parts of bamboo fiber, 6 parts of aluminum dihydrogen phosphate, 2.0 parts of rubber powder, 0.5 parts of starch ether, 0.1 parts of nano titanium oxide, 80 parts of pearl sand, 5 parts of zeolite, 7 parts of expanded pearlite powder and 18 parts of water.
[0050] A bioactive porous ceramic material, the production method of which comprises the following steps:
[0051] Step 1: Prepare the masterbatch. Accurately measure the aluminate cement cementitious material, bamboo fiber, aluminum dihydrogen phosphate, rubber powder, starch ether, and nano-titanium oxide, stir and mix them evenly in a mixer, accurately measure, and package them for storage.
[0052] Step 2: Prepare the batch material. Accurately measure the masterbatch, pearl sand, zeolite, and expanded perlite powder, stir and mix them evenly in a mixer, accurately measure, and package them for storage.
[0053] Step 3: Molding. Assemble the mold, calculate the amount of ingredients, add the ingredients and water into the mortar mixer, stir for 3 minutes, let stand for 10 minutes, continue stirring for 2 minutes, add to the mold, and tamp with a micro vibrator. After 7 days, remove the mold to obtain the blank.
[0054] Step 4: Drying and firing. After the blank is cured for 7 days, it is dried and dehydrated in a dryer at 100℃~110℃ for 8 hours. The dried and dehydrated blank enters the roller kiln for low-temperature firing. During firing, the blank is stacked in a refractory sagger. The firing cycle is 0.5~1 hour, and the maximum temperature is 550℃~580℃. The following reactions will occur during firing:
[0055] Reaction 1: Physical water removal from cement stone, aluminum dihydrogen phosphate, zeolite, bamboo fiber, and expanded perlite powder at 100℃ to 300℃, and the porosity of the dehydrated blank increases;
[0056] Reaction 2: 300-580℃ hydrated calcium hydroxide in cement stone dehydrates and forms active calcium phosphate with aluminum polyphosphate after dehydration of aluminum dihydrogen phosphate, increasing the porosity and strength of the blank; bound water in pearl sand is released;
[0057] Reaction three: 580℃ insulation, pearl sand dehydration, bamboo fiber carbonization, sintering under the action of a small amount of glass liquid phase and aluminum polyphosphate, the cement stone still maintains strength, ensuring the sintered size, strength, activity and porosity.
[0058] Step 5: Testing. Test the size, pore size of the filter material, bulk density, bending strength, water absorption, pure water permeability, pH value of the 24-hour immersion water solution, and dissolved oxygen concentration.
[0059] Example 3
[0060] A bioactive porous ceramic material comprises the following components, measured by weight: 10 parts of aluminate cement gelling material, 2.0 parts of bamboo fiber, 5 parts of aluminum dihydrogen phosphate, 1.8 parts of rubber powder, 0.5 parts of starch ether, 0.2 parts of nano titanium oxide, 70 parts of pearl sand, 10 parts of zeolite, 10 parts of expanded pearlite powder and 20 parts of water.
[0061] A bioactive porous ceramic material, the production method of which comprises the following steps:
[0062] Step 1: Prepare the masterbatch. Accurately measure the aluminate cement cementitious material, bamboo fiber, aluminum dihydrogen phosphate, rubber powder, starch ether, and nano-titanium oxide, stir and mix them evenly in a mixer, accurately measure, and package them for storage.
[0063] Step 2: Prepare the batch material. Accurately measure the masterbatch, pearl sand, zeolite, and expanded perlite powder, stir and mix them evenly in a mixer, accurately measure, and package them for storage.
[0064] Step 3: Molding. Assemble the mold, calculate the amount of ingredients, add the ingredients and water into the mortar mixer, stir for 3 minutes, let stand for 10 minutes, continue stirring for 2 minutes, add to the mold, and tamp with a micro vibrator. After 7 days, remove the mold to obtain the blank.
[0065] Step 4: Drying and firing. After the blank is cured for 7 days, it is dried and dehydrated in a dryer at 100℃~110℃ for 8 hours. The dried and dehydrated blank enters the roller kiln for low-temperature firing. During firing, the blank is stacked in a refractory sagger. The firing cycle is 0.5~1 hour, and the maximum temperature is 550℃~580℃. The following reactions will occur during firing:
[0066] Reaction 1: Physical water removal from cement stone, aluminum dihydrogen phosphate, zeolite, bamboo fiber, and expanded perlite powder at 100℃ to 300℃, and the porosity of the dehydrated blank increases;
[0067] Reaction 2: 300-580℃ hydrated calcium hydroxide in cement stone dehydrates and forms active calcium phosphate with aluminum polyphosphate after dehydration of aluminum dihydrogen phosphate, increasing the porosity and strength of the blank; bound water in pearl sand is released;
[0068] Reaction 3: Keep warm at 580℃, dehydrate pearl sand, carbonize bamboo fiber, and sinter in the presence of a small amount of glass liquid phase and aluminum polyphosphate to ensure sintered size, strength, activity and porosity.
[0069] Step 5: Testing. Test the size, pore size of the filter material, bulk density, bending strength, water absorption, pure water permeability, pH value of the 24-hour immersion water solution, and dissolved oxygen concentration.
[0070] Example 4
[0071] A bioactive porous ceramic material comprises the following components, measured by weight: 10 parts of aluminate cement gelling material, 2.0 parts of bamboo fiber, 4 parts of aluminum dihydrogen phosphate, 1.5 parts of rubber powder, 0.5 parts of starch ether, 0.1 parts of nano titanium oxide, 65 parts of pearl sand, 10 parts of zeolite, 15 parts of expanded pearlite powder and 20 parts of water.
[0072] A bioactive porous ceramic material, the production method of which comprises the following steps:
[0073] Step 1: Prepare the masterbatch. Accurately measure the aluminate cement cementitious material, bamboo fiber, aluminum dihydrogen phosphate, rubber powder, starch ether, and nano-titanium oxide, stir and mix them evenly in a mixer, accurately measure, and package them for storage.
[0074] Step 2: Prepare the batch material. Accurately measure the masterbatch, pearl sand, zeolite, and expanded perlite powder, stir and mix them evenly in a mixer, accurately measure, and package them for storage.
[0075] Step 3: Molding. Assemble the mold, calculate the amount of ingredients, add the ingredients and water into the mortar mixer, stir for 3 minutes, let stand for 10 minutes, continue stirring for 2 minutes, add to the mold, and tamp with a micro vibrator. After 7 days, remove the mold to obtain the blank.
[0076] Step 4: Drying and firing. After the blank is cured for 7 days, it is dried and dehydrated in a dryer at 100℃~110℃ for 8 hours. The dried and dehydrated blank enters the roller kiln for low-temperature firing. During firing, the blank is stacked in a refractory sagger. The firing cycle is 0.5~1 hour, and the maximum temperature is 550℃~580℃. The following reactions will occur during firing:
[0077] Reaction 1: Physical water removal from cement stone, aluminum dihydrogen phosphate, zeolite, bamboo fiber, and expanded perlite powder at 100℃ to 300℃, and the porosity of the dehydrated blank increases;
[0078] Reaction 2: 300-580℃ hydrated calcium hydroxide in cement stone dehydrates to form active calcium oxide, and forms active calcium phosphate with aluminum polyphosphate after dehydration of aluminum dihydrogen phosphate, increasing the porosity and strength of the blank; bound water in pearl sand is released and expanded;
[0079] Reaction 3: Keep warm at 580℃, dehydrate pearl sand, carbonize bamboo fiber, and sinter in the presence of a small amount of glass liquid phase and aluminum polyphosphate to ensure sintered size, strength, activity and porosity.
[0080] Step 5: Testing. Test the size, pore size of the filter material, bulk density, bending strength, water absorption, pure water permeability, pH value of the 24-hour immersion water solution, and dissolved oxygen concentration.
[0081] The performance of the bioactive porous ceramics prepared in the above examples was tested, and the test method and test results are shown below.
[0082] The size and appearance quality are tested by the method specified in GB / T 3810.2 "Test methods for ceramic tiles Part 2: Inspection of size and appearance quality", the pore size of the filter material is tested by the method specified in GB / T 1967-1996 "Test method for pore diameter of porous ceramics", the bulk density is measured by the method specified in GB / T 1966-1996 "Determination method for apparent porosity and bulk density of porous ceramics", the compressive strength is measured by the method specified in GB / T 1964-1996 "Test method for compressive strength of porous ceramics", the flexural strength is measured by the method specified in GB / T 1965-1996 "Test method for flexural strength of porous ceramics", the water absorption and apparent porosity are measured by the method specified in GB / T 3810.3 "Test methods for ceramic tiles Part 3: Determination of water absorption, apparent porosity, apparent relative density and bulk density", and the pure water permeability is measured according to GB / T The test is carried out by the method specified in GB / T 1969-1996 "Test method for permeability of porous ceramics". The pH value of the 24-hour immersion in aqueous solution is determined by the method specified in GB / T 9724 "General rules for determination of pH value of chemical reagents". During the test, the test piece is broken into 100 mesh and immersed in 10% aqueous solution for 24 hours. The dissolved oxygen concentration is determined by the method specified in HJ 506-2009 "Electrochemical probe method for determination of dissolved oxygen in water quality". The product quality should comply with the provisions of GB / T 16533-1996 "General technical conditions for porous ceramic products".
[0083] The test results of the embodiment are shown in Table 1
[0084] Serial number Test content unit Example 1 Example 2 Example 3 Example 4 1 Aperture μm 3.24 3.71 3.63 3.47 2 Test weight g / L 1.38 1.63 1.58 1.47 3 Compression strength MPa 3.71 4.10 4.03 3.88 4 Bending Strength MPa 1.68 2.05 1.98 1.87 5 Apparent porosity % 52.12 47.83 48.87 50.03 6 Water absorption % 35.34 33.78 34.54 34.48 7 Pure water permeability <![CDATA[μm 2 ]]> 0.88 1.10 1.03 0.92 8 pH 8.0 8.0 8.0 8.0
[0085] The bioactive porous ceramics of the present invention can increase the dissolved oxygen concentration of water under sunlight, light or ultraviolet irradiation, provide a healthy living environment for nitrifying bacteria, and improve the nitrification efficiency of nitrifying bacteria. The alkaline components of the bioactive porous ceramics are slowly released and dissolved in water, making the water quality continuously weakly alkaline, which is conducive to the survival of nitrifying bacteria. The porosity of the bioactive porous ceramics ensures physical filtration of water and also improves the aeration process and the dissolution of oxygen. The porosity of the bioactive porous ceramics has good adsorption for microorganisms, which improves the ability of microorganisms to treat sewage.
[0086] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or terminal device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or terminal device. In the absence of further restrictions, the elements defined by the sentence "include..." or "comprise..." do not exclude the existence of other elements in the process, method, article or terminal device including the elements. In addition, in this article, "greater than", "less than", "exceed" and the like are understood to exclude the number itself; "above", "below", "within" and the like are understood to include the number itself.
[0087] Although the above embodiments have been described, once those skilled in the art know the basic creative concepts, they can make additional changes and modifications to these embodiments. Therefore, the above description is only an embodiment of the present invention and does not limit the patent protection scope of the present invention. Any equivalent structure or equivalent process transformation made by using the contents of the specification and drawings of the present invention, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A bioactive porous ceramic material, characterized in that: The invention comprises the following components in parts by weight: 8 to 20 parts of aluminate cement gelling material, 1.0 to 2.0 parts of bamboo fiber, 1 to 7 parts of aluminum dihydrogen phosphate, 1 to 2 parts of rubber powder, 0.1 to 0.5 parts of starch ether, 0.1 to 0.5 parts of nano titanium oxide, 60 to 80 parts of pearl sand, 5 to 10 parts of zeolite powder, 7 to 20 parts of expanded perlite powder and 18 to 22 parts of water.
2. A bioactive porous ceramic material according to claim 1, characterized in that: The pearl sand particle size is 70-140 mesh, and the bulk density is 1567 kg / m 3 .
3. A bioactive porous ceramic material according to claim 1, characterized in that: The zeolite powder is clinoptilolite produced in Shangtianti, Xinyang, with a fineness of less than 10%.
4. The bioactive porous ceramic material according to claim 1, characterized in that: The bulk density of the expanded pearlite powder should be less than 130 kg / m 3 , fineness <10%.
5. The bioactive porous ceramic material according to claim 1, characterized in that: The bamboo fibers have a fiber length of 5 to 10 mm and a diameter of 20 to 30 μm.
6. The bioactive porous ceramic material according to claim 1, characterized in that: The aluminum dihydrogen phosphate is a white powder with a relative density of 2.19 g / cm 3 .
7. The bioactive porous ceramic material according to claim 1, characterized in that: The starch ethers include but are not limited to hydroxyalkyl starch ethers, carboxymethyl starch ethers and cationic starch ethers.
8. A bioactive porous ceramic material according to claim 7, characterized in that: The hydroxyalkyl starch ether has a viscosity of 100000 mPa·s and a fineness of 80 to 100 meshes.
9. The bioactive porous ceramic material according to claim 1, characterized in that: The nano titanium is a white loose powder with anatase crystal form, a particle size of 10 nanometers, a purity greater than 99.9%, and a specific surface area of 70 to 90 m 2 / g.
10. A method for producing a bioactive porous ceramic material according to claims 1 to 9, characterized in that: The method comprises the following steps: Step 1: Prepare the masterbatch, accurately measure the aluminate cement gelling material, bamboo fiber, aluminum dihydrogen phosphate, rubber powder, starch ether, and nano-titanium oxide, stir and mix them evenly in a mixer, accurately measure, and package and store them; Step 2: Prepare the batch material, accurately measure the masterbatch, pearl sand, zeolite, and expanded pearlite powder, stir and mix them evenly in a mixer, accurately measure them, and pack them for storage; Step 3: Forming, assembling the mold, calculating the amount of the batch material, adding the batch material and water into the mortar mixer, stirring for 3 minutes, letting it stand for 10 minutes, continuing to stir for 2 minutes, adding it into the mold, and tamping it with a micro vibrator. After 7 days, remove the mold to obtain the blank; Step 4: Drying and firing. After the blank is cured for 7 days, it is dried and dehydrated in a dryer at 100℃~110℃ for 8 hours. The dried and dehydrated blank is fired at low temperature in a roller kiln. During firing, the blank is stacked in a refractory sagger. The firing cycle is 0.5~1 hour, and the maximum temperature is 550℃~580℃.
Citation Information
Patent Citations
Aquarium filtering material with high porosity and preparation method thereof
CN103030213B
Filter material for aquarium and preparation method of filter material
CN114345012A
Cited By
Process method for producing coal gangue ceramsite by adopting microwave drying
CN120172751A